2020
DOI: 10.7883/yoken.jjid.2019.271
|View full text |Cite
|
Sign up to set email alerts
|

Rat-Bite Fever Due to <i>Streptobacillus moniliformis</i> in a Patient without Bite History: an Unexpected Cause of Consciousness Disturbance

Abstract: Rat-bite fever (RBF) is a zoonotic disease caused by direct contact with rats harboring Streptobacillus moniliformis, Streptobacillus notomytis, or Spirillum minus (1,2). Few studies have reported RBF cases. Therefore, the incidence of RBF is not well understood in Japan. The mortality rate is approximately 10 in undertreated RBF cases (1,3). Of the 3 bacterial causes, S. moniliformis infection typically presents as a triad of relapsing fever, polyarthralgia, and skin rash along with severe diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
3
Order By: Relevance
“…Our patient's history demonstrated no direct rodent‐induced injury. However, transmission via rat feces through either a skin defect, inhalation or ingestion seems likely, as described in the literature [4, 7], given the years of exposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient's history demonstrated no direct rodent‐induced injury. However, transmission via rat feces through either a skin defect, inhalation or ingestion seems likely, as described in the literature [4, 7], given the years of exposition.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of recent case studies on RBF infections, we found strong similarities in incubation period, a triadic constellation of fever, polyarthritis, and rashes, time to final diagnosis and time to symptomatic resolution [7, 13, 14]. Interestingly, many authors report initiating appropriate therapy only after a significant delay – usually, days – until a thorough exposure history is established [13, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Natrium-Polyanetholsulfonat, ein üblicher Bestandteil aerober Blutkulturmedien, kann das Wachstum von Streptobacillus moniliformis hemmen und führt daher zu niedrigen negativen Vorhersagewerten [6] Rattenkot über einen Hautdefekt oder eine Inhalation beziehungsweise Ingestion wahrscheinlich. Entsprechende Übertragungswege sind auch aus der Literatur bekannt [4,7]. Die Prognose des RBF ist abhängig von einer frühzeitigen wirksamen Antibiotikatherapie; fehlende Behandlung ist mit schweren kardialen Komplikationen und Mortalitätsraten von 7-13 % durch Klappenfunktionsstörungen, die in 50 % der Fälle letal sind, assoziiert.…”
Section: Diskussionunclassified
“…Aufgrund der jahrelangen Exposition ist jedoch eine Übertragung durch Rattenkot über einen Hautdefekt oder eine Inhalation beziehungsweise Ingestion wahrscheinlich. Entsprechende Übertragungswege sind auch aus der Literatur bekannt [4, 7].…”
Section: Diskussionunclassified
See 1 more Smart Citation